Pengaruh Disrupsi Teknologi dan Transformasi Terhadap Kinerja Bisnis Perusahaan : Kasus PT.Pos Indonesia (Persero) - Muhammad Amin (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The research objective was to determine the impact of digital disruption and transformation on the business performance of the Pos Indonesia case study. The research method used is quantitative with a survey method by sending questionnaires to the central office and regional offices of Pos Indonesia with 20 respondents. The collected data were analyzed using Smart Partial Least Square version 3.0. Digital disruption and transformation have an impact on business performance. Keywords: Digital Disruption, Transformation, Business Performance